MORPHOTECTONICS OF THE CADIZ-MALAGA SEGMENT, SOUTHERN SPAIN - Cotilla-Rodríguez, Mario Octavio (2016)
We present the results of a morphotectonic research of the Cadiz to Malaga continental segment, which is a western interaction zone between the African and Europe-Asian plates. There is a system of 5 types of Territorial Units (macroblocks= 2, mesoblocks= 2, blocks= 29, microblocks= 44, and nanoblocks= 202) in current space-time relations with a network of 29 main alignments and 32 intersections or junctions. Fifty-nine percent of the blocks are very active or active, and the territory has a mean value of ~0.03 fractures/km2 with 63 scarps. The most active zones are between Barbate-Torrecera-Sierra de las Cabras (in Cádiz) and Ronda-Embalse Gudaltela-Cabras-Villalon (in Málaga). This Cadiz-Malaga segment has similar characteristics to those determined for the adjacent zone of Almería-Córdoba-Granada-Jaén-Murcia. All data are in a GIS.